Chemotyping of the Fusarium graminearum Isolates and Variation in Aggressiveness against Wheat Heads - F. Mert-Türk1; R. Gencer; F.; Kahriman (Journal of Animal and Plant Sciences, 2014)
Fusarium head blight (FHB), caused mainly by Fusarium graminearum, is a devastating disease of wheat and other small grain cereals. FHB lowers grain yield and quality, and contaminates grain with mycotoxins, predominantly trichotecenes i.e nivalenol (NIV), deoxynivalenol (DON). A survey conducted at three Provinces in Turkey for FHB and 17 isolates were identified as F. graminearum using morphological and molecular markers. A PCR assay was carried out to identify the chemotypes of the isolates. Using Tri13 gene cluster, all 17 isolates that were identified to 15-AcDON type of DON chemotype. None of the isolates displayed 3-ADON or NIV chemotypes. In order to assess variation in aggressiveness among isolates, all isolates were inoculated to a susceptible wheat spikes at field conditions and disease severity and a thousand kernel weight were measured. Aggressiveness (measured as FHB severity or TKW) differed significantly among 17 F. graminearum isolates inoculated onto wheat spikes of FHB susceptible cultivar Gönen (P=0,05). Means of FHB severity ranged from 39.75 to 86.33%, averaging 63.29% in total. Reduction in TKW was also reduced significantly by different isolates. Differences in aggressiveness among isolates may due to genetic recombination, mutation or selection in the surveyed area.
Keywords: Fusarium graminearum; mycotoxins; chemotypes; DON; NIV; pathogenicity; aggressiveness